2021
DOI: 10.1002/bkcs.12447
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of catechol‐conjugated chitosan and its application as an additive for cement mortar

Abstract: We synthesized catechol-conjugated chitosan (CCC) to study its usefulness as a construction material additive in cement mortar. The degree of catechol conjugation (DOC cat ) of the synthesized CCC was determined to be approximately 14% by UV-vis and 1 H NMR spectroscopy. Furthermore, the hydroxyl and amine groups in CCC could play a crucial role in hydrogen bonding, metal coordination, and cross-linking processes via interaction with adducts from cement mortar. In this study, we observed an improvement in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…Chitosan, as a natural biopolymer, has good biocompatibility and biodegradability [4,5]. Its degradation products are non-toxic, highly adsorptive, and noncarcinogenic, and are widely used in the biomedical, wastewater treatment, flocculation, and civil engineering fields [6][7][8][9]. The previous literature [10,11] has shown that chitosan, as a polymer structure added to cement-based materials, has great application prospects in improving the early fracture toughness of cement-based materials, improving the rheological properties of cement-based materials, and regulating the heat release process of cement hydration due to the interaction between its molecular chains and the surface of cement particles.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan, as a natural biopolymer, has good biocompatibility and biodegradability [4,5]. Its degradation products are non-toxic, highly adsorptive, and noncarcinogenic, and are widely used in the biomedical, wastewater treatment, flocculation, and civil engineering fields [6][7][8][9]. The previous literature [10,11] has shown that chitosan, as a polymer structure added to cement-based materials, has great application prospects in improving the early fracture toughness of cement-based materials, improving the rheological properties of cement-based materials, and regulating the heat release process of cement hydration due to the interaction between its molecular chains and the surface of cement particles.…”
Section: Introductionmentioning
confidence: 99%
“…A superfície da quitosana contém um grande número de grupos amino e hidroxila, que podem ser facilmente modificados para produzir uma resposta a diferentes comportamentos [27]. Aliado ao seu baixo custo, sua utilização tem sido bastante investigada no meio científico ao longo dos anos, e não só na área da construção civil em compósitos cimentícios [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], como também em outras aplicações, tais como, na medicina [44,45], na agricultura [46,47] e cosméticos [48,49].…”
Section: Introductionunclassified
“…Modification of the R 3 position, the primary amine, has been extensively used for synthesizing DA derivatives . Various functional molecules were conjugated at this site through amide-bond-forming reactions. However, the conjugation to the R 3 position prevents indole formation, which is another key intermediate for surface coating; thus, the coating efficiency is not as high that compared to DA. , The indole formation inhibition may be due to the decrease in nitrogen nucleophilicity. The nitrogen in amides is less nucleophilic than that in free amines because of the nitrogen lone pair resonance stabilization by the carbonyl group.…”
Section: Introductionmentioning
confidence: 99%